Analgesic efficacy of sodium salicylate in an amphotericin B induced bovine synovitis-arthritis model - Kotschwar, Jamie Lee (Kansas State University, 2009)
Lameness is a common, costly, and painful affliction in cattle at all production levels. There are currently no compounds specifically approved for analgesia in cattle in the United States. We hypothesized that intra-articular amphotericin B produces a controlled, transient synovitis-arthritis in cattle and that this model would allow characterization of the analgesic effects of intravenous sodium salicylate. This study examined the efficacy of sodium salicylate for providing analgesia in an amphotericin B-induced bovine synovitis/arthritis model utilizing ten male Holstein calves, 4-6 months old, and weighing approximately 250 kg. The study used a repeated measures partial cross-over design with 2 phases consisting of 3 treatment periods within each phase. Calves were blocked by weight and randomly assigned to sodium salicylate (50mg/kg intravenously) or placebo group for phase 1. In period 1, lameness induction was simulated with a needle-prick of the coronary band, followed by drug or placebo administration. At predetermined timepoints, serial blood samples for cortisol and salicylate concentrations, electrodermal activity measurements, heart rates, and pressure mat data were collected. Visual lameness scores were recorded by a blinded observer. In period 2, lameness was induced with injection of amphotericin B into the distal interphalangeal joint followed by drug or placebo administration with sample collection as previously described. In period 3, drug or placebo was administered to the respective calves with sample collection. After a 10-day washout, Phase 2 was conducted with treatments crossed over between groups. Cortisol and salicylate samples were analyzed by competitive chemiluminescent immunoassay and fluorescence polarization immunoassay, respectively. The pharmacokinetic data were analyzed using compartmental analysis. Mean intravenous salicylate apparent volume of distribution (V[subscript]d) was 0.2 ± 0.005 L/kg, total body clearance (CL[subscript]B) was 4.3 ± 0.2 mL/min*kg, and elimination half life (T[subscript]1/2 el) was 36.9 ± 1.2 minutes. The repeated measures data were analyzed based on a univariate split-plot approach with a random effects-mixed model. Differences in stance phase duration and serum cortisol concentration values were seen between both periods and treatment group*periods; differences in heart rate, contact surface area, and contact pressure values were seen between periods, suggesting that our lameness model was effective. No differences were seen between treatment groups. When analyzed by visual lameness score, differences were seen in heart rate, contact surface area, contact pressure, and cortisol concentrations. Area under the time-effect curves, determined using the trapezoidal rule, had results similar to the repeated measures data, except for a difference in period for electrodermal activity. This amphoterecin B-induced synovitis/arthritis model is a useful tool for studying changes associated with lameness in cattle. Sodium salicylate was not effective in providing analgesia following lameness.
Keywords: pain; salicylate; Biology, Animal Physiology (0433); Biology, Veterinary Science (0778)